Indicações de deformações neotectônicas na bacia do rio pardo-SP através de análises de parâmetros fluviomorfométricos e de imagens SRTM - Guedes, Ivan Claudio [UNESP]; Morales, Norberto [UNESP]; Etchebehere, Mario Lincoln de Carlos [UNESP]; Saad, Antônio Roberto (My University, 2015)
This paper aims to outline possible neotectonic deformation in the Rio Pardo hydrographic basin - RPHB based onstream morphometry and SRTM image analysis. The RPHB is located in the São Paulo State Western Plateau, with a geologicsubstrate that encompasses basalts of the Serra Geral Formation (~132 Ma) and sedimentary rocks of the Bauru Group (UpperCretaceous), with local Cenozoic sediments, including Quaternary alluvium and alluvial terraces, colluvial mantles, as well as loosesandy aprons with both uncertain ages and derivation. The stream morphometric analyses undertaken in this study comprise thestream-longitudinal profiles, the RDE ratios (Slope vs. Length indexes) and nickpoint alignments in association with drainage orrelief lineaments. The RPHB is elongated and its widest portion seems clearly controlled by WNW lineaments, that provide thesubdivision of the basin into larger morphostructural blocks and might represent neotectonic reactivations of Guapiara Alignment.The boundary with the Rio Turvo basin shows up controlled by a significant ENE lineament beam. Although this direction is notnoticeable in the rest of the basin, it probably represents an important structural limit, composing a rhombohedral pattern at thewidest portion of the valley. Stream-morphometry anomalies (especially those that reflect rising tectonic behavior) are concentratedon the southern flank of the basin, which is narrower than right band. This region appears to be being uplifted, as opposed to theother side, where the thicker regolith and alluvium are most expressive, indicating subsidence conditions that favor accumulation ofthe southern flank erosion products. The RPHB appears to have been amplified by the capture process incorporating most of thewider portion of the current basin. In that process, there was base level lowering, watercourses incisions and alluvial terraceformation in the lower valley. As a general result, those processes led to interfluve fragmentation, as reflected in the spatialdistribution of thicker regolith portions interpreted from SRTM textural photoanalysis. The conjunction of lineaments separatingareas with different degrees of dissection, stream-morphometric anomaly concentrations, nickpoint alignments, plus the arrangementof areas with the best preserved regolith elicites a brittle morphotectonic model delineated by structural blocks with different verticaldisplacements.
Indications of neotectonic deformations in the Rio Pardo-SP basin through the analyses of fluvial morphometric parameters and SRTM images